DAMPAK DATA SECURITY TERHADAP ADOPSI PENGGUNAAN FINTECH BAGI GEN Z - Andini, Rindi; Hariyani, Happy Febrina (Program Studi Ekonomi Pembangunan, 2024)
This research aims to determine empirically the influence of perceived ease of use (PEU), perceived usefulness (PU), and data security (DAS) on Fintech adoption intentions through Fintech promotion (FP), and customer trust (CT) in FINTECH for Gen Z . Data from 100 people aged between 15 and 25 years who have filled out the questionnaire. This quantitative research uses a cross-sectional research design, and data is analyzed using the Partial Least Square (PLS)-Structural Equation Modeling (SEM) technique. This research will add to the existing literature on Fintech service adoption by providing new understanding of the factors that determine user behavior in adopting Fintech services. Therefore, this research can help regulators regarding data security through proper IT infrastructure can help increase Fintech adoption. Additionally, the findings of this research also demonstrate the importance for Fintech innovators to understand their customers' attitudes regarding data transparency and security.